AN ERROR ANALYSIS IN USING SIMPLE PAST TENSE OF NARRATIVE TEXT IN JUNIOR HIGH SCHOOL STUDENTS - Hisasmaria Hisasmaria (Madani: Jurnal Politik dan Sosial Kemasyarakatan, 2024)
The objective of the research was to find out the kinds of error in using simple past tense of narrative text and dominant error made by the first grade students of SMP Negeri 1 Buntulia. This research employed descriptive research. The population of the research was the first grade students of SMP Negeri 1 Buntulia. The sample consisted of 20 students taken from each class in Academic Year 2023/2024. The data were collected through the students’ written test of narrative. The result of the research showed that there were 374 total error that the students made which were classified into four categories based on surface strategy taxonomy (SST). The error of omission was 90 errors, the error of addition was 48 errors, the errors of misformation was231 errors and the errors of misordering was 5 errors. The dominant error of the students were in misformation category. It can be seen from the percentage of the result where misformation were 62%, then followed by the error of omission with 24%, the error of addition with 13%, and the error of misordering with 1%. Based on the result of the research, it can be concluded that the first grade students of SMP Negeri 1 Buntulia had many errors in writing narrative text especially in using simple past tense. The students need more practice in using simple past tense in order to make them familiar with it and they can arrange a good narrative text.